3D nitrogen-doped graphene foam with encapsulated germanium/nitrogen-doped graphene yolk-shell nanoarchitecture for high-performance flexible Li-ion battery - Runwei Mo (Nature Portfolio, 2017)
The development of materials for energy storage hinges on the design of electrodes with large capacity, flexibility, fast charge–discharge rate and long cycling lifetime. Here, the authors develop electrodes based on nitrogen doped graphene with encapsulated Ge quantum dots with yolk-shell architecture.